BURNOUT AMONG HEALTH STUDENTS AND PROFESSIONALS: COPING STRATEGIES BASED ON INTEGRATIVE AND COMPLEMENTARY PRACTICES - Clara de Medeiros Brilhante, Anna; Bento das Chagas, Douglas; Rodrigues dos Santos, Leonardo; Costa de Azevedo Mello, Emmanuella; Moisés de Lima Júnior, Erivar; Mikaelly Silva Pinto, Juliana (Revista Gênero e Interdisciplinaridade, 2026)
Burnout syndrome has emerged as a significant mental health issue among students and healthcare professionals, characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment. This condition is associated with prolonged exposure to academic and occupational stressors, such as workload overload, performance pressure, competitiveness, exposure to human suffering, and insufficient institutional support. This study aimed to analyze burnout among healthcare students and professionals, focusing on triggering factors and coping strategies. This is a theoretical-reflective study based on a critical analysis of national and international scientific literature. The findings indicate a high prevalence of burnout, particularly among health students, with significant impacts on emotional well-being, academic performance, and quality of care. Adaptive coping strategies, such as social support, self-care practices, mindfulness, and psychological support, were associated with stress reduction, whereas maladaptive strategies were linked to worsening conditions. The need for institutional interventions is highlighted, including psychological support, workload restructuring, and strengthening support networks. It is concluded that burnout is a multifactorial phenomenon requiring an integrated approach that combines individual and organizational strategies to promote mental health and foster more resilient and prepared professionals.